1999
DOI: 10.2307/2640786
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Driving X Chromosomes and Resistance Factors in Experimental Populations of Drosophila simulans

Abstract: Sex-ratio drive is a particular case of meiotic drive, described in several Drosophila species, that causes males bearing driving X chromosome to produce a large excess of females in their progeny. In Drosophila simulans, driving X chromosomes and resistance factors located on the Y chromosome and on the autosomes have been previously reported. In this paper, we report the study of the dynamics of sex-ratio factors in experimental populations. We followed the evolution in frequency of driving X chromosomes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…Studies that report no difference in fertility between SR and standard males are either a large scale population cage experiment (Capillon and Atlan 1999) or a field study (Beckenbach 1996), which estimate fertility effects from overall population results, whereas those demonstrating differences are detailed studies of individual flies (Wu 1983a;Atlan et al 2004). Clearly the methodology used can have significant impacts on the results, suggesting that the fertility differences are only revealed in circumstances that allow multiple mating.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that report no difference in fertility between SR and standard males are either a large scale population cage experiment (Capillon and Atlan 1999) or a field study (Beckenbach 1996), which estimate fertility effects from overall population results, whereas those demonstrating differences are detailed studies of individual flies (Wu 1983a;Atlan et al 2004). Clearly the methodology used can have significant impacts on the results, suggesting that the fertility differences are only revealed in circumstances that allow multiple mating.…”
Section: Animalsmentioning
confidence: 99%
“…The second potential source of bias is the preferential reporting of studies that found a particular relationship. However, four of the papers included only report fertility as a secondary point and did not mention it in the abstract (Hartl et al 1967;Capillon and Atlan 1999;Tao et al 2001;Orr and Irving 2005). In two further papers, fertility was not a major focus of the paper (Wood and Newton 1991;Beckenbach 1996), and in two others a large number of male traits were examined in which fertility was included (Beukeboom 1994;Snook et al 2000).…”
Section: Potential Effects Of Reporting Biasmentioning
confidence: 99%
“…Alternatively, new sex-ratio X chromosomes may have appeared re-currently in populations, and Africa is simply a region where ecological and demographic conditions favor their spread. In contrast, the invasion dynamics of Y-linked and autosomal suppressors challenged with sex-ratio X chromosome in experimental populations suggests that they have little or no deleterious impact (Capillon & Atlan, 1999) and work in progress CJutier, unpublished) has so far failed to detect any detrimental effects on fitness ofY-linked suppressors. According to the first scenario, which we shall call the 'historical' scenario, the whole system could be at a transient stage, which may eventually result in the non-African populations becoming more similar to the current African ones, and possibly their reversion to a no-distorter/no-suppressor stage.…”
Section: Geographical Variationmentioning
confidence: 99%
“…A total suppressor, for example, has a five-fold advantage over a sensitive Y chromosome transmitted to 10% of the offspring. Using experimental populations with fixed sex-ratio X chromosomes, into which polymorphic autosomal suppressors were introduced, Carvalho, Peixoto and Klaczoko (1989) and Capillon and Atlan (1999) have provided direct evidence of this process in D. mediopunctata and D. simulans, respectively. If suppressors of various strengths appear, the final stage will correspond to the fixation of the most powerful.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation